Economic status, social status, and rate of internationalization in US law firms. Issue 2 (4th May 2018) - Powell, K. Skylar; Rhee, Mooweon
ABSTRACT: We note that in the legal industry, socially constructed status may be an especially powerful type of firm position, and may also relate to internationalization through opening offices in new foreign markets. Hence, in this analysis we offer the first effort to simultaneously consider relationships between socially derived firm status and internationalization, and economic status and internationalization in a legal industry context. Specifically, we use longitudinal data on large US corporate law firms from 1984 to 2008. We find an inverted U-shaped relationship between social status and rate of internationalization. Additionally, we identify an inverted U-shaped relationship between economic status, or domestic market share, and rate of internationalization.